DNA Hypermethylation af a Panel Of Genes as an Urinary Biomarker For Bladder Cancer Diagnosis - Georgopoulos, Petros; Papaioannou, Maria; Markopoulou, Soultana; Fragou, Aikaterini; Kouvatseas, George; Apostolidis, Apostolos (Urology Journal, 2021)
Purpose: Several studies have shown frequent changes in DNA methylation in bladder cancer (BCa), which vary among different geographical areas. The aim of this study is to examine the diagnostic accuracy of a panel of DNA methylation biomarkers in a Greek clinical setting contributing to the development of a universal panel of urine biomarkers. Materials and Methods: Individuals with primary BCa and control individuals matching the gender, age and smoking status of the cancer patients were recruited. DNA methylation was assessed for the gene promoters of RASSF1, RARB, DAPK, TERT and APC in urine samples collected by spontaneous urination using quantitative Methylation Specific PCR (qMSP). All genes had been previously separately associated with BCa. Results: Fifty patients and 35 healthy controls were recruited, with average age of 70.26 years and average smoking status of 44.78 pack-years. In the BCa group, DNA methylation was detected in 27 (61.4%) samples. RASSF1 was methylated in 52.2% of samples. Only 3 (13.6%) samples from the control group were methylated, all in the RASSF1 gene promoter. The specificity and sensitivity of this panel of genes to diagnose BCa was 86% and 61% respectively. The RASSF1 gene could diagnose BCa with specificity 86.4% and sensitivity 52.3%. Conclusion: Promoter DNA methylation of this panel of five genes could be further investigated as urine biomarker for the diagnosis of BCa. The RASSF1 could be a single candidate biomarker for predicting BCa patients versus controls. Studies are required in order to develop a geographically adjusted diagnostic biomarker for BCa.